Deep Learning Based Twitter Sentiment Analysis (International Journal of Food and Nutritional Sciences, 2022)
To summarize reviews of a product, an extensively used approach is Aspect-based textmining which is applied on tweets or review data. With the help of Twitter sentimentdetectors (TSDs) we can obtaina finer answer to assess a product in terms of quality andservice. Social media has become a necessarymeans of communication in our daily lives. Ifwe consider Twitter, most of the tweets are usually unstructured, non-formal, and it lackslabeled data like ratings, emojis, different categories, images, hashtags, videos etc. whichmakes it laborious for product opinion mining.